Suicide attempts and completions in Veterans Affairs nursing home care units and long‐term care facilities: a review of root‐cause analysis reports. (30th September 2015) - Mills, Peter D.; Gallimore, Bradley I.; Watts, B. Vince; Hemphill, Robin R.
Abstract : Objective: Suicide was the 10th leading cause of death for Americans in 2010. The suicide rate is highest among men who are aged 75 and older. The prevalence of suicidal behavior in nursing homes and long‐term care (LTC) facilities was estimated to be 1%. This study describes the systemic vulnerabilities found after suicidal behavior in LTC facilities as well as steps to decrease or mitigate the risk. Method: This is a retrospective review of root‐cause analysis (RCA) reports of suicide attempts and completions between 1 January 2000 and 31 December 2013 in the Veterans Health Administration LTC and nursing home care units. The RCA reports of suicide attempts and completions were coded for patient demographics, method of attempt or completion, root causes, and actions developed to address the root cause. Results: Thirty‐five RCA reports were identified. The average age was 65 years, 11 had a previous suicide attempt, and the primary mental health diagnoses were depression, posttraumatic stress disorder, and schizophrenia. The primary methods of self‐harm were cutting with a sharp object, overdose, and strangulation. Conclusions: It is recommended that all staff members are aware of the signs and risk factors for depression and suicide in this population and should systematically assess and treat mental disorders. In addition, LTC facilities should have a standard protocol for evaluating the environment for suicide hazards and use interdisciplinary teams to promote good communication about risk factors identified among patients. Finally, staff should go beyond staff education and policy to make clinical changes at the bedside. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.